Combining ability analysis for seed yield and yield components in castor (Ricinus communis L.): COMBINING ABILITY ANALYSIS IN CASTOR - K K PATEL; HARSHAL E. PATIL (Journal of Oilseeds Research, 2013)
The genetic analysis was done through a line x tester design involving 70 castor (Ricinus communis L.) hybrids generated by crossing 5 pistillate lines with 14 pollen parents. The combining ability analysis for yield and its components revealed that both additive and non-additive genetic variance were significantly influenced by environment. The preponderance of additive gene action was observed for the control of daysto 50 % flowering and days to 50 % maturity of main raceme as well as number of nodes up to main raceme. Non-additive gene effect was predominant for the characters, plant height and oil content. The parents SKP-8, 103745, 1379, SKP-93, TMV-5, Aruna, SH-72 and SK2-8A were good general combinersfor imparting earliness, former three as well as VP-1 were good general combiner forshort plantstature. The parents SH-72, SK 2-BA, SKP-82,JH-128, SH-41 and 48-1 were good general combiners for oil content. The estimates of gca effects suggested that parents SKP-93, SKP-82, 48-1, Aruna, SPS-35-9B,JI-77 and JH-128 were good general combinersforseed yield and several yield components viz., 100 seed weight, effective branches/plant, number of capsulesin main raceme and length of main raceme. The good specific cross combinations for yield viz., SKP-8 x TMV-5, VP-l x SKI-41 and SKP 25 x 1379 were also identified as superior hybrids for earliness, high oil content and short plant stature, respectively and may be exploited for commercial cultivation. The hybrids SKP-8 x TMV-5, SKP-25 x JH- 128 and SKP-82 x 48-1 with significant positive sca effect for seed yield could be exploited for development of hybrids and new inbred as well as pistilate lines in castor. The potence ratio of genetic variance suggested preponderance of non-additive gene effect for inheritance of the seed yield/plant, number of capsules in main raceme and number of effective branches.